2016
DOI: 10.1002/jae.2500
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation, Tax Avoidance, and the Price Elasticity of Gasoline Demand

Abstract: Least-squares estimates of the response of gasoline consumption to a change in the gasoline price are biased toward zero, given the endogeneity of gasoline prices. A seemingly natural solution to this problem is to instrument for gasoline prices using gasoline taxes, but this approach tends to yield implausibly large price elasticities. We demonstrate that anticipatory behavior provides an important explanation for this result. Gasoline buyers increase purchases before tax increases and delay purchases before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(49 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…For example, anticipating a future tax for high-CO 2 -emitting vehicles, consumers could decide to purchase such vehicles before the tax increase. This behavior would bias estimates of the effects of taxes on registrations, similarly to the bias introduced by anticipated fuel tax changes (Coglianese et al 2017). Based on our reading of Her Majesty's Treasury documentation of each year's budget and on examining news coverage about the budget and VED debate prior to the final budget approval, we believe that anticipation effects are unlikely to be important in this setting (see Appendix C).…”
Section: Empirical Modelmentioning
confidence: 99%
“…For example, anticipating a future tax for high-CO 2 -emitting vehicles, consumers could decide to purchase such vehicles before the tax increase. This behavior would bias estimates of the effects of taxes on registrations, similarly to the bias introduced by anticipated fuel tax changes (Coglianese et al 2017). Based on our reading of Her Majesty's Treasury documentation of each year's budget and on examining news coverage about the budget and VED debate prior to the final budget approval, we believe that anticipation effects are unlikely to be important in this setting (see Appendix C).…”
Section: Empirical Modelmentioning
confidence: 99%
“…Kayser [46] investigated the USA case and concluded that taxes on gasoline had an important effect on the decrease of gasoline demand. Tiezzi and Verde [47], Coglianese et al [5], Rivers and Schaufele [48] and Filippini and Heimsch [49] also examined the issues affecting gasoline demand in different countries. It was concluded that tax rate had a statistically significant effect on gasoline demand.…”
Section: Literature Review On Gasoline Demandmentioning
confidence: 99%
“…Because all private cars, vehicles and urban buses use gasoline, its price is essential for these parties. For instance, people who have private cars spend a substantial portion of their income on gasoline [5]. Therefore, any increase in the price can have an important effect on their gasoline demand behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which firms will be able to exercise market power in Mexico's deregulated petroleum markets thus depends on the price elasticity of demand for gasoline and diesel. Most studies have found that demand for gasoline and other fuels is relatively inelastic, particularly in the short-run (Hughes et al, 2008;Li et al, 2014;Coglianese et al, 2017;Levin et al, 2017). On the surface, this evidence would appear to imply a considerable potential for market power in Mexico's retail petroleum markets.…”
Section: Market Powermentioning
confidence: 99%